Efficacy of a polyherbal formula for controlling lice infestation in chickens and goats in backyard farming system in Romania - Coroian, Mircea; Hociotă, Cristinel-Cornel; Varga, Erzsébet; Fülöp, Ibolya; Fazakas, Mihaly; Györke, Adriana (Frontiers in Animal Science, 2024)
IntroductionLice infestation negatively impacts the welfare and productivity of domestic animals. This study aimed to evaluate the efficacy of a commercial polyherbal formula (PHF) containing Asarum europaeum, Lavandula angustifolia, Artemisia absinthium, and Tanacetum vulgare in managing lice infestations in chickens and goats within a backyard farming system in Romania.MethodsThe PHF was analyzed using high-performance liquid chromatography (HPLC) to determine its phytochemical composition. Chickens and goats with confirmed lice infestations were treated with the PHF by spraying it on the entire body. Treatments were administered three times at 14-day intervals for goats and at both 14- and 7-day intervals for chickens. Lice infestations were assessed in experimental groups before each treatment by counting the collected lice specimens.ResultsHPLC analysis identified key compounds in PHF: kaempferol (336.25 mg/ml), quercetin (88.38 mg/ml), epicatechin (43.98 mg/ml), and catechin (9.43 mg/ml). The PHF effectively controlled chewing lice in both chickens and goats, achieving a mortality rate of 76–98% in chickens and 96% in goats. However, the PHF was not effective against sucking lice in goats. A significant reduction in lice infestation (75% in chickens) was observed when the PHF was applied at 7-day intervals. No adverse reactions were noted in treated animals.DiscussionThe polyherbal formula demonstrated promising efficacy against chewing lice in chickens and goats, supporting its potential use as an alternative to chemical treatments, especially in organic farming settings. The findings suggest that this PHF could be a viable option for managing lice infestations in domestic animals, particularly where organic practices are prioritized.